2019
DOI: 10.3390/a12090176
|View full text |Cite
|
Sign up to set email alerts
|

Online EEG Seizure Detection and Localization

Abstract: Epilepsy is one of the three most prevalent neurological disorders. A significant proportion of patients suffering from epilepsy can be effectively treated if their seizures are detected in a timely manner. However, detection of most seizures requires the attention of trained neurologists—a scarce resource. Therefore, there is a need for an automatic seizure detection capability. A tunable non-patient-specific, non-seizure-specific method is proposed to detect the presence and locality of a seizure using elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…These combined metrics were previously used for detecting seizures. 38 , 42 Each feature provides a different view of brain-network interactions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These combined metrics were previously used for detecting seizures. 38 , 42 Each feature provides a different view of brain-network interactions.…”
Section: Methodsmentioning
confidence: 99%
“…The distances are calculated and extracted as coherency measurements in different frequency bands using a variety of distance metrics, including previously used metrics for detecting and localizing seizures. 38 The metrics investigated include some that combine measures of connectivity as well as measures of power in the frequency bands (the metrics are described in the Supplementary Materials). All coherencies in the frequency domain are studied over different scalp regions of the brain to capture any significant spatial differences between regions in classifying participants with a concussion and those without concussion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they also focused on the reduction of ECoG electrodes. Mansouri et al [135] proposed an algorithm for Seizure localization, which was tested on 10 sec of EEG dataset from Karuniya University. Here, they have taken the small-size dataset, because recording usually takes several hours.…”
Section: Seizure Localizationmentioning
confidence: 99%
“…Studies that are addressing real-time epileptic seizure detection techniques can be found in [145][146][147][148][149]. Hanosh et al [145] used Passive Infrared Sensors (PIR) for realtime epileptic seizure detection during sleep.…”
Section: Epileptic Seizure Detectionmentioning
confidence: 99%